Monocyte-derived and M1 macrophages from ankylosing spondylitis patients released higher TNF-α and expressed more IL1B in response to BzATP than macrophages from healthy subjects - Akhtari, Maryam; Zargar, Seyed Jalal; Vojdanian, Mahdi; Jamshidi, Ahmadreza; Mahmoudi, Mahdi (Scientific reports, 2021)
Macrophages participate in the pathogenesis of ankylosing spondylitis (AS) by producing inflammatory cytokines. Extracellular adenosine triphosphate (eATP), released during cell stress, acts through purinergic receptors (P2XR and P2YR) and induces inflammatory responses. We investigated the effect of 2ʹ(3ʹ)-O-(4-benzoyl benzoyl) ATP (BzATP) (a prototypic agonist of P2X7R) on the production of inflammatory cytokines in both monocyte-generated (M2-like) and M1 macrophages from patients and controls. Macrophages were differentiated from isolated periphery-monocytes (n = 14 in each group) by macrophage colony-stimulating factor (M-CSF). Using LPS and IFN-γ, macrophages were skewed toward M1 type and were treated with BzATP. Gene expression and protein release of IL-1β, IL-23, and TNF-α were evaluated by real-time PCR and ELISA methods respectively before and after treatment. BzATP significantly increased the protein release of TNF-α and the expression of TNFA and IL1B in monocyte-generated macrophages. Besides, BzATP treatment significantly upregulated IL1B expression, reduced TNFA and IL23A expression, and TNF-α release in M1 macrophages from both groups. Monocyte-generated and M1 macrophages from AS patients released higher TNF-α and expressed more IL1B in response to the same concentration of BzATP treatment respectively. Based on our results, AS macrophages were more sensitive to BzATP treatment and responded more intensively. Besides, the diverse effects of BzATP on monocyte-derived and M1 macrophages in our study may represent the differed inflammatory properties of these two groups of macrophages in response to eATP in the body.